STUDY OF THE EFFECT OF SCHOOL ENVIRONMENT ON THE EDUCATIONAL ACHIEVEMENT OF STUDENTS STUDYING AT SECONDARY LEVEL - Savita; Singh, Bindu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
For students studying at secondary level, this environment forms the basis of their educational, mental and social development. School environment includes teacher-student relationship, influence of classmates, educational resources, and administrative policies. These elements can positively or negatively affect the learning ability of students and their educational achievements. The relationship between teacher and students plays a central role in educational achievements. An inspiring and supportive teacher can instill confidence and interest in studies in students. On the contrary, harsh or neglectful attitude of teachers can affect the performance of students. The influence of classmates is also important because positive peer groups can motivate students to perform better while negative influence can weaken their self-esteem and educational goals. Resources available in the school such as libraries, laboratories, playgrounds and technical equipment promote the educational success of students. Adequate resources help in providing practical and experiential education to students. Also, the environment of the classrooms, such as cleanliness, lighting and seating, affects the concentration and learning ability of students. The administrative policies and disciplinary measures of the school also affect the academic achievement of students. A progressive and inclusive administrative system provides a sense of freedom and cooperation to the students. Also, the examination system, methods of evaluation and the structure of the curriculum also guide the performance of students. School environment also has an impact on mental and emotional health. A stress-free and inspiring environment encourages students to use their full potential. On the contrary, an atmosphere of pressure and insecurity can affect the mental health and academic achievements of students. Ultimately, the impact of school environment on the academic achievement of students is wide-ranging and multi-faceted. It is essential that schools provide an environment that not only encourages academic success but also helps in the overall development of students. For this, teachers, parents and administration should work together to create a positive and encouraging environment.